2012
DOI: 10.1634/theoncologist.2011-0446
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making in Pediatric Allogeneic Blood and Marrow Transplantation: What If There Is No Decision to Make?

Abstract: Learning Objectives: After completing this course, the reader will be able to: When the alternative to medical treatment is likely death, ask parents and children whether they agree to the medical plan rather than suggesting they are sharing in “a decision.” Use the model of shared decision in appropriate settings, that is, those in which a bona fide choice exists. This article is available for continuing medical education credit at http://CME.TheOncologist.com Introduction. Shared decision‐making between he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 19 publications
0
46
0
1
Order By: Relevance
“…The parent study focused on family decision-making in pediatric HSCT and included interviewing children undergoing HSCT and their family members (ie, parents, grandparents, siblings, half siblings, and cousins) at 4 time points over the course of a year. 33 Eligible families had a child undergoing HSCT with at least 1 sibling between the ages 9 and 22 years in the home. This report analyzed the second interview, which was conducted 5 to 9 months posttransplant, giving the families time to develop their own strategies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parent study focused on family decision-making in pediatric HSCT and included interviewing children undergoing HSCT and their family members (ie, parents, grandparents, siblings, half siblings, and cousins) at 4 time points over the course of a year. 33 Eligible families had a child undergoing HSCT with at least 1 sibling between the ages 9 and 22 years in the home. This report analyzed the second interview, which was conducted 5 to 9 months posttransplant, giving the families time to develop their own strategies.…”
Section: Methodsmentioning
confidence: 99%
“…33 We supplemented the secondary analysis with prospective interviews with family members of children, adolescents, and young adults (“children” henceforth is understood to include adolescents and young adults) undergoing HSCT and pediatric transplant health care providers. This study aims to provide an account of sibling issues during HSCT and the strategies families used to help them.…”
mentioning
confidence: 99%
“…Lack of choice, whether a concern or not, may imply the need for an advocate to help the family understand the medical options, but this information may be most effective coming from the treating physician. 20 From the donor perspective, "no choice" becomes concerning in the case of "forced no choice." 11 One 9-year-old donor did regret donation, but her expressed concerns were absence of her mother and believing that she was not the best HLA match, not lack of choice.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case where procedures have become routinized in health care, such as a ‘diagnostic’ performed following the identification of a breast lump . Also, where patients see no acceptable alternative, they may implicitly assume that no decision‐making opportunity exists; when faced with a decision about paediatric allogeneic blood and marrow transplantation, 81% of parents reported that there was no decision to be made . In such examples, the use of the terms ‘decision’ or ‘option’ may not be appropriate because patients believe they are ‘agreeing to a plan’ rather than encountering a decision‐making point …”
Section: Patient‐reported Measures Of Shared Decision Makingmentioning
confidence: 99%